234k views
21 votes
Find the locus of a point such that the sum of its distance from the point ( 0 , 2 ) and ( 0 , -2 ) is 6.

~Thanks in advance ! ​

User Sahar
by
5.5k points

1 Answer

10 votes

Answer:


\displaystyle (x^2)/(5)+(y^2)/(9)=1

Explanation:

We want to find the locus of a point such that the sum of the distance from any point P on the locus to (0, 2) and (0, -2) is 6.

First, we will need the distance formula, given by:


d=√((x_2-x_1)^2+(y_2-y_1)^2)

Let the point on the locus be P(x, y).

So, the distance from P to (0, 2) will be:


\begin{aligned} d_1&=√((x-0)^2+(y-2)^2)\\\\ &=√(x^2+(y-2)^2)\end{aligned}

And, the distance from P to (0, -2) will be:


\displaystyle \begin{aligned} d_2&=√((x-0)^2+(y-(-2))^2)\\\\ &=√(x^2+(y+2)^2)\end{aligned}

So sum of the two distances must be 6. Therefore:


d_1+d_2=6

Now, by substitution:


(√(x^2+(y-2)^2))+(√(x^2+(y+2)^2))=6

Simplify. We can subtract the second term from the left:


√(x^2+(y-2)^2)=6-√(x^2+(y+2)^2)

Square both sides:


(x^2+(y-2)^2)=36-12√(x^2+(y+2)^2)+(x^2+(y+2)^2)

We can cancel the x² terms and continue squaring:


y^2-4y+4=36-12√(x^2+(y+2)^2)+y^2+4y+4

We can cancel the y² and 4 from both sides. We can also subtract 4y from both sides. This leaves us with:


-8y=36-12√(x^2+(y+2)^2)

We can divide both sides by -4:


2y=-9+3√(x^2+(y+2)^2)

Adding 9 to both sides yields:


2y+9=3√(x^2+(y+2)^2)

And, we will square both sides one final time.


4y^2+36y+81=9(x^2+(y^2+4y+4))

Distribute:


4y^2+36y+81=9x^2+9y^2+36y+36

The 36y will cancel. So:


4y^2+81=9x^2+9y^2+36

Subtracting 4y² and 36 from both sides yields:


9x^2+5y^2=45

And dividing both sides by 45 produces:


\displaystyle (x^2)/(5)+(y^2)/(9)=1

Therefore, the equation for the locus of a point such that the sum of its distance to (0, 2) and (0, -2) is 6 is given by a vertical ellipse with a major axis length of 3 and a minor axis length of √5, centered on the origin.

User Stephan Ronald
by
5.4k points